2014
DOI: 10.1093/ntr/ntu284
|View full text |Cite
|
Sign up to set email alerts
|

Change in Body Weight Does Not Mediate the Relationship Between Exercise and Smoking Cessation Among Weight-Concerned Women Smokers

Abstract: Introduction: Exercise has received attention as a method to prevent or reduce postcessation weight gain. However, little is known about how weight changes following quit attempts contribute to the relationship between exercise and smoking cessation. The present study assessed how exercise relates to cessation and whether initial changes in exercise after quitting smoking promote cessation through attenuated weight gain. Methods: Weight-concerned women smokers (N = 342) receiving cessation treatment provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Smoking level was assessed using cigarettes per month and daily vs. non-daily smoking status in Landrau-Cribbs et al (2015) and as cigarettes per day in Martin et al (2016). Emery et al (2015) emerged in the initial literature search in the present study, but was not included in this table or in the 17 total articles identified in our search as their sample consisted of women endorsing postcessation weight gain concern, but no data on postcessation weight gain concern were reported (Emery, Levine, Cheng, & Marcus, 2015). a There was a significant weight concern*NRT interaction for women, such that higher weight concerns predicted greater probability of abstinence among those who were prescribed a combination of nicotine patch and oral nicotine replacement, but not among women taking only oral forms. b Participants were African American, light smokers randomized to receive either bupropion and health education (HE) counseling for smoking cessation or to a placebo and HE comparison condition. c Landrau-Cribbs et al (2015) also adjusted for general weight concerns and stage of change (i.e., motivation) in their model examining the postcessation weight gain concern-cessation relationship. d Smoking frequency was assessed using percent of smoking days and number of cigarettes smoked per day. e Higher weight concern importance scores significantly predicted a higher percentage of smoking days at 1-month follow-up, but did not predict 3-month percent smoking days, 1- or 3-month cigarettes smoked per day, or 1- or 3-month 7-day PP. f Higher weight concerns significantly predicted longer delay to quit date, but did not significantly predict continuous abstinence at 12 months. Landrau-Cribbs et al (2015) and Pankova et al (2016) used Meyers et al’s (1997) assessment of 2-lb weight gain increments, but used an increasing trend starting at 0–2 lb vs. using Meyers et al’s decreasing trend starting at 18–20 lb. …”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Smoking level was assessed using cigarettes per month and daily vs. non-daily smoking status in Landrau-Cribbs et al (2015) and as cigarettes per day in Martin et al (2016). Emery et al (2015) emerged in the initial literature search in the present study, but was not included in this table or in the 17 total articles identified in our search as their sample consisted of women endorsing postcessation weight gain concern, but no data on postcessation weight gain concern were reported (Emery, Levine, Cheng, & Marcus, 2015). a There was a significant weight concern*NRT interaction for women, such that higher weight concerns predicted greater probability of abstinence among those who were prescribed a combination of nicotine patch and oral nicotine replacement, but not among women taking only oral forms. b Participants were African American, light smokers randomized to receive either bupropion and health education (HE) counseling for smoking cessation or to a placebo and HE comparison condition. c Landrau-Cribbs et al (2015) also adjusted for general weight concerns and stage of change (i.e., motivation) in their model examining the postcessation weight gain concern-cessation relationship. d Smoking frequency was assessed using percent of smoking days and number of cigarettes smoked per day. e Higher weight concern importance scores significantly predicted a higher percentage of smoking days at 1-month follow-up, but did not predict 3-month percent smoking days, 1- or 3-month cigarettes smoked per day, or 1- or 3-month 7-day PP. f Higher weight concerns significantly predicted longer delay to quit date, but did not significantly predict continuous abstinence at 12 months. Landrau-Cribbs et al (2015) and Pankova et al (2016) used Meyers et al’s (1997) assessment of 2-lb weight gain increments, but used an increasing trend starting at 0–2 lb vs. using Meyers et al’s decreasing trend starting at 18–20 lb. …”
Section: Tablementioning
confidence: 99%
“…Smoking level was assessed using cigarettes per month and daily vs. non-daily smoking status in Landrau-Cribbs et al (2015) and as cigarettes per day in Martin et al (2016). Emery et al (2015) emerged in the initial literature search in the present study, but was not included in this table or in the 17 total articles identified in our search as their sample consisted of women endorsing postcessation weight gain concern, but no data on postcessation weight gain concern were reported (Emery, Levine, Cheng, & Marcus, 2015).…”
Section: Tablementioning
confidence: 99%
“…Women smokers who already reported an active lifestyle have been shown to have more success quitting and more gradual rates of returning to smoking [43]. According to a metaanalysis by Spring and colleagues [39], combined smoking cessation plus weight treatment resulted in significantly higher short-term abstinence and significantly lower weight gain than did smoking treatment alone.…”
Section: Introductionmentioning
confidence: 99%
“…Despite multiple recommendations, the prevalence of smoking in people with and without diabetes remains comparable [11]. One of the commonest arguments against quitting in people with diabetes is the risk of weight gain and worsening glycaemic control after quitting [12, 13]. Some studies have demonstrated a positive correlation between weight gain and increased HbA1c after quitting [14, 15].…”
Section: Introductionmentioning
confidence: 99%